Precoated sand for casting and preparation method thereof

By combining modified phenolic resin with quartz sand and modified fostilide powder and graphite, the problems of insufficient high-temperature performance of coated sand and difficult to control the spray coating process are solved, and the efficient anti-stick sand and sintering effect without secondary coating in manganese steel volute casting is achieved, reducing costs and improving casting quality.

CN119702946APending Publication Date: 2025-03-28CHENGDE DONGWEI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411917281.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

During the casting process of manganese steel volute shells, the high-temperature performance of existing coated sand is insufficient, resulting in problems with sand sticking, pores and roughness, the spray coating process is difficult to control, and the bead sand is costly and has strong application limitations.

Method used

Modified phenolic resin and quartz sand are used to work synergistically to coat the surface of quartz sand, and modified fosperidine powder and graphite are added to adjust the curing time and curing temperature, improve the hardness and water resistance of the coating layer, form a heat insulation barrier, and prevent sand adhesion and sintering.

Benefits of technology

During the casting of manganese steel volute shells, no secondary coating is required, which effectively prevents sand sticking and sintering, reduces costs, reduces environmental pollution, and improves the surface finish and quality of the castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207105640000021
    Figure BDA0005207105640000021
  • Figure BDA0005207105640000041
    Figure BDA0005207105640000041
  • Figure BDA0005207105640000111
    Figure BDA0005207105640000111
Patent Text Reader

Abstract

The invention discloses precoated sand for casting and a preparation method of the precoated sand, and relates to the technical field of precoated sand for casting. 0 to 0.01 part of a silane coupling agent; 0 to 0.5 part of bisphenol A type epoxy resin; 1.5 to 2.5 parts of modified phenolic resin; 0.1 to 0.5 part of an additive; 0-1 part of a curing agent; 0 to 0.5 part of a lubricant; wherein the modified phenolic resin is obtained through reaction of phenolic resin and acrylic acid-2-hydroxyethyl ester, and the mass ratio of the phenolic resin to the acrylic acid-2-hydroxyethyl ester is (7-8): (2-3). According to the precoated sand for casting, the hardness and the water resistance of a coating layer on the surface are greatly improved, secondary coating is not needed in the subsequent shell mold casting process, and the problems of sand burning, sintering and the like in the casting process can be effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foundry coated sand, and in particular to foundry coated sand and a preparation method thereof. Background Art

[0002] With the continuous development and progress of casting technology and machinery manufacturing industry, people's development of cast steel alloy materials and improvement of smelting technology, steel castings are increasingly widely used, and the output of steel castings is increasing year by year.

[0003] In the prior art, in the casting process of manganese steel volutes, coated sand shell casting is generally used. The manganese in high manganese alloy steel easily forms MnO at the interface, which easily reacts with SiO2 in silica sand to form MnO·SiO2 or 2MnO·SiO2, and its residual strength is higher than that of iron olivine 2FeO·SiO2, so the sand sticking phenomenon is more serious. The furnace temperature during the casting of high manganese steel is generally 1750°C, and the pouring temperature is 1620°C. The heat resistance of the sand mold (shell) is extremely high. In order to make up for the insufficient high temperature performance of the coated sand, the coating is applied to solve the problems of sand sticking, pores and roughness on the surface of the casting. At present, the most commonly used is zircon powder coating / magnesia coating. The steel casting needs to be dipped or brushed as a whole, which is time-consuming, labor-intensive and costly. To obtain castings with smooth surfaces, the coating must not only have good performance in use, but also have excellent high-temperature performance, ensuring that the coating does not crack or fall off when the temperature changes drastically, and that the physical and chemical properties are stable and cannot react with the liquid metal. The coating must also be easy to peel off from the surface of the casting. Only in this way can the integrity of the coating be maintained at high temperatures and play an effective isolation role between the molten metal and the sand mold. In addition, the coating must also have low gas emission to avoid pores in the casting.

[0004] However, spraying also brings a series of problems. The spraying process is difficult to control. An unreasonable spraying process will cause other defects to the casting. For example, the coating is too thin to prevent sintering, the coating is too thick and easy to peel off, causing slag inclusions in the casting, and incomplete drying of the coating will cause pores and vein defects in the casting. Spraying may reduce the dimensional accuracy of the casting. There are environmental pollution problems in the coating manufacturing, spraying and drying processes.

[0005] Another common way to solve the sintering problem of steel castings is to use ceramsite. Ceramsite, also known as fused ceramsite, is a special foundry sand. Its main component is Al2O3, with high refractoriness (≥1790℃), low thermal conductivity and small thermal expansion. Ceramsite particles are round and point-contacted between sintered layer particles, which can effectively reduce the strength of the sintered layer and is suitable for various metal castings. However, the cost of ceramsite is very high and its application has obvious limitations. Summary of the invention

[0006] In order to solve the problem of sand sticking in the manganese steel casting process, and at the same time solve the problems of spraying coatings on shell mold cast steel and the limitations of gem sand, the present invention provides a low-cost coated sand for casting, and no secondary coating is required in the shell mold casting process, and it can also effectively prevent sand sticking, sintering and other problems in the casting process.

[0007] In order to achieve the above object, the present invention provides a coated sand for casting, comprising the following raw materials in parts by weight:

[0008]

[0009] The modified phenolic resin is a modified phenolic resin obtained by reacting phenolic resin with 2-hydroxyethyl acrylate, and the mass ratio of phenolic resin to 2-hydroxyethyl acrylate is (7-8): (2-3).

[0010] Compared with the prior art, the coated sand of the present invention uses a modified phenolic resin to cooperate with other components to coat the surface of quartz sand. The modified phenolic resin of the present invention is a phenolic resin modified by 2-hydroxyethyl acrylate. By introducing 2-hydroxyethyl acrylate into the phenolic resin, it cooperates with other components, and under the above-mentioned specific ratio, the curing time and curing temperature of the phenolic resin on the surface of quartz sand can be adjusted, and finally the hardness and water resistance of the coating layer on the surface of the coated sand are greatly improved, so that the coated sand of the present invention does not need secondary coating in the subsequent shell casting process, and can effectively prevent the problems of sand sticking and sintering in the casting process.

[0011] Furthermore, the additives include modified forsterite powder and graphite, and the mass ratio of the modified forsterite powder and the graphite added is (0.5-6): (4-9.5).

[0012] Compared with the prior art, the additive of the present invention includes modified forsterite powder and graphite, graphite has good high temperature resistance, modified forsterite powder has good thermal conductivity, slow and uniform thermal expansion, strong resistance to metal oxide corrosion, high chemical stability, and the modified forsterite powder, graphite and other components work together to make the coated sand of the present invention have better thermal stability and heat resistance, while compressive strength, tensile strength and toughness are greatly improved, and the overall mechanical properties are superior, and finally the coating layer on the surface of the coated sand can form a heat insulation barrier between quartz sand and molten steel, effectively preventing problems such as sticking sand and sintering during the casting process. In addition, under the synergistic effect of the additive of the present invention and other components, the processing performance of the coated sand is also improved, making it easier to operate during the molding process, while the anti-ultraviolet and anti-aging properties can be improved, the service life can be extended, and the surface smoothness or antistatic properties can also be improved.

[0013] Furthermore, the modified forsterite powder is a modified forsterite powder obtained by modifying forsterite powder with 4-hydroxybutyl acrylate, and the mass ratio of the added amount of 4-hydroxybutyl acrylate to the forsterite powder is (0.1-0.5): (1-2).

[0014] Compared with the prior art, the modified forsterite powder of the present invention is the modified forsterite powder obtained by modifying forsterite powder with 4-hydroxybutyl acrylate. The introduction of 4-hydroxybutyl acrylate can improve the dispersibility of the forsterite powder, improve its compatibility with other components, reduce agglomeration, and evenly disperse when mixed with other components of the present invention, so that the components of the coating layer on the surface of the coated sand of the present invention are evenly distributed and the thickness of the film layer is uniform.

[0015] Furthermore, the particle size of the modified forsterite powder is 300-600 mesh; the particle size of the graphite is 300-600 mesh.

[0016] Furthermore, the curing agent is hexamethylenetetramine.

[0017] Furthermore, the lubricant is calcium stearate.

[0018] Furthermore, the silane coupling agent is any one of KH550 and KH560.

[0019] A second aspect of the present invention provides a method for preparing coated sand for casting, comprising the following steps:

[0020] S1: calcining quartz sand;

[0021] S2: sieving the quartz sand calcined in step S1 and cooling it to a first temperature;

[0022] S3: After the quartz sand cooled in step S2 is further cooled to a second temperature, a silane coupling agent, bisphenol A epoxy resin, modified phenolic resin, additives, a curing agent and a lubricant are added in sequence, and the mixture is stirred and mixed to obtain coated sand.

[0023] Compared with the prior art, after the coated sand is prepared by the preparation method of the present invention, there is no need to apply thermal insulation coating in the later steel casting production process, which not only reduces the process procedures and costs, but also reduces environmental pollution problems.

[0024] Furthermore, in step S1, the calcination process is as follows: the calcination temperature is 700-930° C., and the calcination time is 10-30 min.

[0025] Furthermore, in step S2, the first temperature is 170-190°C.

[0026] Furthermore, in step S3, the second temperature is 150-160°C.

[0027] Compared with the prior art, the above technical scheme limits the second temperature to 150-160°C. After the quartz sand is roasted, the temperature is lowered to this temperature range. Within this temperature range, bisphenol A epoxy resin, modified phenolic resin, etc. maintain a certain fluidity and viscosity, which not only allows the raw materials to be fully mixed within this temperature range to wrap the quartz sand, thereby forming a uniform coating layer on the surface of the quartz sand, but also saves energy and utilizes the residual heat after the quartz sand is roasted to complete the mixing of the raw materials.

[0028] Furthermore, the preparation method of the modified forsterite powder comprises the following steps: mixing 4-hydroxybutyl acrylate with water, adding forsterite powder, impregnating with ultrasonic stirring at 25-80° C., filtering and drying to obtain the modified forsterite powder;

[0029] The mass ratio of 4-hydroxybutyl acrylate, forsterite powder and water is (0.1-0.5): (1-2): (8-9); the process parameters of ultrasonic stirring are: ultrasonic frequency 20-80kHz, stirring speed 100-500rpm, and drying temperature 80-120°C.

[0030] Furthermore, the preparation method of the modified phenolic resin is as follows: providing phenolic resin, 2-hydroxyethyl acrylate and an initiator, wherein the mass ratio of the phenolic resin, 2-hydroxyethyl acrylate and the initiator is (70-80): (20-30): (0.5-3);

[0031] The phenolic resin and the 2-hydroxyethyl acrylate are reacted in the presence of the initiator at a reaction temperature of 60 to 100° C. and a pH value of 7 to 9 for 2 to 12 hours to obtain a modified phenolic resin; wherein the initiator is any one of benzoyl peroxide, dibenzoyl peroxide, and azobisisobutyronitrile. DETAILED DESCRIPTION

[0032] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] The present invention provides a coated sand for casting, comprising the following raw materials in parts by weight:

[0034]

[0035] The modified phenolic resin is a modified phenolic resin obtained by reacting phenolic resin with 2-hydroxyethyl acrylate, and the mass ratio of phenolic resin to 2-hydroxyethyl acrylate is (7-8): (2-3).

[0036] The present invention discloses a film-coated sand for casting, which is coated on the surface of quartz sand by using a modified phenolic resin and other components in synergy. The modified phenolic resin of the present invention is a phenolic resin modified by 2-hydroxyethyl acrylate, which is introduced into the phenolic resin, and the active sites (such as hydroxymethyl) present in the phenolic resin are utilized to allow the 2-hydroxyethyl acrylate molecules to be grafted onto the phenolic resin by free radical initiation and other methods. The modified phenolic resin and other components act in synergy, and under the above-mentioned specific ratio, the curing time and curing temperature of the film layer on the surface of the quartz sand can be adjusted, and the hardness and water resistance of the film layer on the surface of the film-coated sand can be improved. Under the synergy of the above-mentioned components and specific ratios, the present invention discloses a film-coated sand for casting, which does not require secondary coating in the subsequent shell casting process, and can effectively prevent the problems of sand sticking and sintering in the casting process. The mass ratio of phenolic resin to 2-hydroxyethyl acrylate is further set to (7-8): (2-3), preferably (7.5-8): (2-2.5), for example, 7:3, 7.8:2.8, 7.6:2.5, 7.5:2, 8:2. Under the specific mass ratio of phenolic resin to 2-hydroxyethyl acrylate, the phenolic resin is combined with a specific amount of 2-hydroxyethyl acrylate molecules, so that the flexibility, water resistance, mechanical strength and processing performance of the coated sand for casting of the present invention are greatly improved.

[0037] In some optional embodiments, the additive includes modified forsterite powder and graphite, and the mass ratio of the modified forsterite powder and the graphite addition is (0.5-6): (4-9.5), preferably (5-6): (4-5). Specifically, the mass ratio of the modified forsterite powder and the graphite addition can be 0.5:9.5, 2.5:6, 4:8, 5:5 or 6:4.

[0038] The additive used in the present invention works in synergy with other components to form a film on the surface of quartz sand. The additive of the present invention includes modified forsterite powder and graphite, and graphite has good high temperature resistance; the modified forsterite powder has good thermal conductivity, which can effectively improve the refractory performance of the coated sand, improve the thermal stability and thermal shock resistance of the coated sand, reduce cracks and breakage caused by temperature changes, and at the same time, the porosity of the sand core prepared using the coated sand of the present invention is improved, thereby improving the air permeability of the sand core, facilitating the discharge of gas during the casting process, and reducing pore defects. Under the specific mass ratio of modified forsterite powder and graphite, and in synergy with other components, the coating layer on the surface of the coated sand can eventually form a heat insulation barrier between the quartz sand and the molten steel, so that the coated sand of the present invention has better refractoriness, thermal stability, air permeability, anti-sand sticking and lubricity, thereby improving the yield and casting quality during the casting process. In addition, with the synergistic effect of the additives of the present invention and other components, the processing performance of the coated sand of the present invention is improved, making it easier to operate during the molding process. At the same time, the anti-ultraviolet and anti-aging properties can be enhanced, the service life can be extended, and the surface smoothness or anti-static properties can be improved. The performance of the coated sand can be significantly improved without significantly increasing the cost, thereby improving the economic benefits.

[0039] In some optional embodiments, the modified forsterite powder is a modified forsterite powder obtained by modifying the forsterite powder with 4-hydroxybutyl acrylate, and the mass ratio of the added amount of 4-hydroxybutyl acrylate to the forsterite powder is (0.1-0.5):(1-2), preferably (0.1-0.2):(1-1.5). Specifically, the mass ratio of the added amount of 4-hydroxybutyl acrylate to the forsterite powder can be 0.1:2, 0.1:1.5, 0.3:1.6, 0.2:1 or 0.5:1.

[0040] The modified forsterite powder of the present invention is the modified forsterite powder obtained by modifying forsterite powder with 4-hydroxybutyl acrylate. Under the specific mass ratio of the above-mentioned 4-hydroxybutyl acrylate and forsterite powder, 4-hydroxybutyl acrylate, forsterite powder and water are fully mixed, and stirred at 25-80°C in an ultra-high temperature so that the hydroxyl (-OH) of the 4-hydroxybutyl acrylate and the active sites on the surface of the forsterite powder, such as the hydroxyl (-OH) and oxygen anions, fully undergo bonding, and the 4-hydroxybutyl acrylate is adsorbed and coated on the surface of the forsterite powder to form the modified forsterite powder, thereby improving the dispersibility of the forsterite powder, improving its compatibility with other components, reducing agglomeration, and evenly dispersing when mixed with other components of the present invention, so that the components of the coating layer on the surface of the coated sand for casting of the present invention are evenly distributed and have uniform thickness.

[0041] In some optional embodiments, the particle size of the modified forsterite powder is 300-600 mesh; the particle size of the graphite is 300-600 mesh. Within the above particle size range, the modified forsterite powder and graphite can be more evenly distributed in the coating layer of the coated sand, thereby improving the refractoriness and thermal stability of the coated sand, forming a uniform and continuous coating layer structure on the surface of the coated sand, and reducing pores and cracks.

[0042] In some optional embodiments, the curing agent and the lubricant may be selected from the curing agent and the lubricant commonly used in the art, for example, the curing agent is hexamethylenetetramine, etc., and the lubricant is calcium stearate, etc.

[0043] In some optional embodiments, the silane coupling agent may be a silane coupling agent commonly used in the art, for example, the silane coupling agent is any one of KH550 and KH560.

[0044] In a second aspect of the present invention, a method for preparing coated sand for casting is provided, comprising the following steps:

[0045] S1: calcining quartz sand.

[0046] Add quartz sand into a roasting furnace at a temperature of 700-930°C and roast for 10-30 minutes to make the sand particles undergo phase change and expansion.

[0047] Calcination of quartz sand at the above temperature and time can effectively remove impurities on the surface of quartz sand, improve the purity of quartz sand, and provide energy for subsequent raw material mixing. If the temperature is too low and the time is too short, impurities on the surface of quartz sand cannot be effectively removed; if the temperature is too high and the time is too long, not only will the quartz sand partially melt, resulting in adhesion between particles, but also a waste of energy.

[0048] Quartz sand will undergo phase change during roasting. The quartz sand after phase change treatment will have greatly reduced loss on ignition and gas emission, which can effectively reduce casting defects caused by expansion during high-temperature pouring (casting). This step of the process allows the coated sand for cast steel to have a silica sand content of more than 85%, rather than 98% of the original sand. This is because the roasting process can cause the quartz sand to undergo phase change while removing the low-melting-point substances on the surface in advance. The surface of the quartz sand is shaped, and when it is made into a sand core (shell) in the future, it will have better strength and air permeability.

[0049] Furthermore, in order to better implement the present invention, the quartz sand can be screened before being roasted, and a suitable screen can be selected for screening according to the requirements of the final coated sand product to be prepared, so as to prepare materials for preparing coated sand that meets the requirements.

[0050] S2: sieving the quartz sand obtained after roasting in step S1 and cooling it.

[0051] The quartz sand obtained after calcination in step S1 is sieved, cooled to above 170° C., preferably 170-190° C., and directly put into the sand mixing kettle.

[0052] The purpose of screening the quartz sand is to remove some dust impurities and broken sand produced during the roasting process, and then cool it to prepare for the subsequent sand mixing. The screen can be selected according to the requirements for the particle size of the coated sand product, which is not limited here. The roasted sand with a certain temperature is directly put into the sand mixing kettle. The residual temperature after roasting is still above 170℃. The purpose is to use the residual temperature of roasting to directly mix the sand later, which can make more efficient use of energy.

[0053] S3: After cooling the quartz sand obtained in step S2 to 150-160°C, add silane coupling agent, bisphenol A epoxy resin, modified phenolic resin, additives, curing agent and lubricant in sequence, stir and mix evenly, cool, and sieve to obtain coated sand. The above stirring speed can be selected according to actual needs, as long as the purpose of uniform mixing can be achieved, and it is not limited here; the screening conditions are selected according to the particle size of the coated sand to be prepared, and it is not limited here. Among them,

[0054] (1) When the quartz sand is cooled to 150-160°C, the raw materials are added in sequence at this temperature. At this time, the bisphenol A epoxy resin, modified phenolic resin, etc. maintain a certain fluidity and viscosity, which not only allows the raw materials to be fully mixed within this temperature range, but also forms a uniform coating layer on the surface of the quartz sand.

[0055] (2) The preparation method of the modified phenolic resin is as follows: phenolic resin, 2-hydroxyethyl acrylate and initiator are mixed in a mass ratio of (70-80): (20-30): (0.5-3), preferably (75-80): (20-25): (0.5-1), and reacted for 2-12 hours at a reaction temperature of 60-100° C. and a pH value of 7-9 in the presence of the initiator to obtain the modified phenolic resin. The initiator of the reaction is any one of benzoyl peroxide, dibenzoyl peroxide and azobisisobutyronitrile.

[0056] Under the above mass ratio and process conditions, the phenolic resin and 2-hydroxyethyl acrylate are fully contacted, mixed and reacted, and the 2-hydroxyethyl acrylate molecules are fully grafted onto the phenolic resin to prepare the modified phenolic resin.

[0057] (3) The additives include modified forsterite powder and graphite, and the preparation method of the modified forsterite powder includes the following steps: mixing 4-hydroxybutyl acrylate with water, adding forsterite powder, impregnating with ultrasonic stirring at 25-80° C., filtering and drying to obtain the modified forsterite powder;

[0058] Among them, the mass ratio of 4-hydroxybutyl acrylate, forsterite powder and water is (0.1-0.5): (1-2): (8-9), preferably (0.1-0.2): (1-1.5): (8-9), and the process parameters of ultrasonic stirring are: ultrasonic frequency of 20-80kHz, stirring speed of 100-500rpm, and drying temperature of 80-120°C.

[0059] Under the above mass ratio and process conditions, the particles of forsterite powder are fully in contact with 4-hydroxybutyl acrylate, and 4-hydroxybutyl acrylate can be completely adsorbed on the surface of forsterite powder to prepare modified forsterite powder.

[0060] In order to better illustrate the technical solution of the present invention, the present invention also provides the following specific embodiments.

[0061] The materials used in the following examples and comparative examples are all commercially available materials.

[0062] Embodiment 1:

[0063] A coated sand for casting, comprising the following raw materials in parts by weight:

[0064] 100 parts of quartz sand, 0.01 parts of silane coupling agent KH550, 0.5 parts of bisphenol A epoxy resin, 2.0 parts of modified phenolic resin, 0.1 parts of additives, 1 part of urotropine, and 0.5 parts of calcium stearate.

[0065] The process is as follows: after quartz sand is roasted at 900°C for 10 minutes, it passes through a cooling screen to screen out dust impurities and broken sand, and then enters a bucket elevator after cooling to 170°C. The bucket elevator directly puts the quartz sand into a sand mixing kettle. When the temperature drops to 150°C, bisphenol A epoxy resin, modified phenolic resin, additives, hexamethylenetetramine, and calcium stearate are added in sequence. After mixing and stirring evenly, the mixture is taken out of the kettle, cooled to room temperature, and sieved through a sieve according to product requirements to obtain coated sand.

[0066] In this embodiment, the preparation method of the additive is as follows:

[0067] After mixing 4-hydroxybutyl acrylate with water, forsterite powder is added, ultrasonic stirring and impregnation are performed at 25°C, and modified forsterite powder is obtained after filtering and drying. The mass ratio of 4-hydroxybutyl acrylate, forsterite powder and water is 0.1:2:9, and the process parameters of the ultrasonic stirring are: ultrasonic frequency is 30kHz, stirring speed is 250rpm, and the drying temperature is 96°C. The modified forsterite powder of 300-400 meshes and the graphite of 300-400 meshes are uniformly mixed in a mass ratio of 4:8 to obtain an additive.

[0068] The preparation method of modified phenolic resin is as follows:

[0069] Phenolic resin, 2-hydroxyethyl acrylate and initiator benzoyl peroxide were mixed in a mass ratio of 70:30:3, and reacted for 10 hours at a reaction temperature of 75° C. and a pH value of 7 in the presence of the initiator to obtain a modified phenolic resin.

[0070] Embodiment 2:

[0071] A coated sand for casting, comprising the following raw materials in parts by weight:

[0072] 100 parts of quartz sand, 0 parts of silane coupling agent, 0.5 parts of bisphenol A epoxy resin, 2.0 parts of modified phenolic resin, 0.2 parts of additives, 1 part of urotropine, and 0.5 parts of calcium stearate.

[0073] The process is as follows: after quartz sand is roasted at 700°C for 20 minutes, it passes through a cooling screen to screen out dust impurities and broken sand, and then enters a bucket elevator after cooling to 180°C. The bucket elevator directly puts the quartz sand into a sand mixing kettle. When the temperature drops to 160°C, bisphenol A epoxy resin, modified phenolic resin, additives, hexamethylenetetramine, and calcium stearate are added in sequence. After mixing and stirring evenly, the mixture is taken out of the kettle, cooled to room temperature, and sieved through a sieve according to product requirements to obtain coated sand.

[0074] In this embodiment, the preparation method of the additive is as follows:

[0075] After mixing 4-hydroxybutyl acrylate with water, forsterite powder is added, ultrasonic stirring and impregnation are performed at 50°C, and modified forsterite powder is obtained after filtering and drying. The mass ratio of 4-hydroxybutyl acrylate, forsterite powder and water is 0.2:1:8, and the process parameters of the ultrasonic stirring are: ultrasonic frequency is 50kHz, stirring speed is 100rpm, and the drying temperature is 105°C. The modified forsterite powder of 400-500 mesh and the graphite of 400-500 mesh are uniformly mixed in a mass ratio of 6:4 to obtain an additive.

[0076] The preparation method of modified phenolic resin is as follows:

[0077] Phenolic resin, 2-hydroxyethyl acrylate and initiator azobisisobutyronitrile were mixed in a mass ratio of 75:20:0.5, and reacted for 12 hours at a reaction temperature of 100° C. and a pH value of 8.2 in the presence of the initiator to obtain a modified phenolic resin.

[0078] Embodiment 3:

[0079] A coated sand for casting, comprising the following raw materials in parts by weight:

[0080] 100 parts of quartz sand, 0.01 parts of silane coupling agent KH560, 0.5 parts of bisphenol A epoxy resin, 2.0 parts of modified phenolic resin, 0.2 parts of additives, 1 part of urotropine, and 0.5 parts of calcium stearate.

[0081] The process is as follows: after quartz sand is roasted at 930°C for 30 minutes, it passes through a cooling screen to screen out dust impurities and broken sand, and then enters a bucket elevator after cooling to 175°C. The bucket elevator directly puts the quartz sand into a sand mixing kettle. When the temperature drops to 155°C, bisphenol A epoxy resin, modified phenolic resin, additives, hexamethylenetetramine, and calcium stearate are added in sequence. After mixing and stirring evenly, the mixture is taken out of the kettle, cooled to room temperature, and sieved through a sieve according to product requirements to obtain coated sand.

[0082] In this embodiment, the preparation method of the additive is as follows:

[0083] After mixing 4-hydroxybutyl acrylate with water, forsterite powder is added, ultrasonic stirring and impregnation are performed at 80°C, and modified forsterite powder is obtained after filtering and drying. The mass ratio of 4-hydroxybutyl acrylate, forsterite powder and water addition is 0.1:1.5:9, and the process parameters of the ultrasonic stirring are: ultrasonic frequency is 20kHz, stirring speed is 360rpm, and the drying temperature is 80°C. The modified forsterite powder of 500-600 mesh and the graphite of 500-600 mesh are uniformly mixed in a mass ratio of 5:5 to obtain an additive.

[0084] The preparation method of modified phenolic resin is as follows:

[0085] Phenolic resin, 2-hydroxyethyl acrylate and initiator azobisisobutyronitrile were mixed in a mass ratio of 80:20:0.5, and reacted for 6 hours at a reaction temperature of 60° C. and a pH value of 7.5 in the presence of the initiator to obtain a modified phenolic resin.

[0086] Embodiment 4:

[0087] A coated sand for casting, comprising the following raw materials in parts by weight:

[0088] 100 parts of quartz sand, 0.01 parts of silane coupling agent KH550, 0.5 parts of bisphenol A epoxy resin, 1.5 parts of modified phenolic resin, 0.5 parts of additives, 1 part of urotropine, and 0.5 parts of calcium stearate.

[0089] The process is as follows: after quartz sand is roasted at 850°C for 25 minutes, it passes through a cooling screen to screen out dust impurities and broken sand, and then enters a bucket elevator after cooling to 190°C. The bucket elevator directly puts the quartz sand into a sand mixing kettle. When the temperature drops to 152°C, bisphenol A epoxy resin, modified phenolic resin, additives, hexamethylenetetramine, and calcium stearate are added in sequence. After mixing and stirring evenly, the mixture is taken out of the kettle, cooled to room temperature, and sieved through a sieve according to product requirements to obtain coated sand.

[0090] In this embodiment, the preparation method of the additive is as follows:

[0091] After mixing 4-hydroxybutyl acrylate with water, forsterite powder is added, ultrasonic stirring and impregnation are performed at 60°C, and modified forsterite powder is obtained after filtering and drying. The mass ratio of 4-hydroxybutyl acrylate, forsterite powder and water is 0.5:1:8, and the process parameters of the ultrasonic stirring are: ultrasonic frequency is 70kHz, stirring speed is 500rpm, and the drying temperature is 120°C. The modified forsterite powder of 300-400 mesh and the graphite of 400-500 mesh are uniformly mixed at a mass ratio of 0.5:9.5 to obtain an additive.

[0092] The preparation method of modified phenolic resin is as follows:

[0093] Phenolic resin, 2-hydroxyethyl acrylate and initiator azobisisobutyronitrile were mixed in a mass ratio of 76:25:2.3, and reacted for 4 hours at a reaction temperature of 85° C. and a pH value of 9 in the presence of the initiator to obtain a modified phenolic resin.

[0094] Embodiment 5:

[0095] A coated sand for casting, comprising the following raw materials in parts by weight:

[0096] 100 parts of quartz sand, 0.01 parts of silane coupling agent KH560, 0 parts of bisphenol A epoxy resin, 2.5 parts of modified phenolic resin, 0.1 parts of additives, 1 part of urotropine, and 0.5 parts of calcium stearate.

[0097] The process is as follows: after quartz sand is roasted at 880°C for 15 minutes, it passes through a cooling screen to screen out dust impurities and broken sand, and then enters a bucket elevator after cooling to 185°C. The bucket elevator directly puts the quartz sand into a sand mixing kettle. When the temperature drops to 158°C, bisphenol A epoxy resin, modified phenolic resin, additives, hexamethylenetetramine, and calcium stearate are added in sequence. After mixing and stirring evenly, the mixture is taken out of the kettle, cooled to room temperature, and sieved through a sieve according to product requirements to obtain coated sand.

[0098] In this embodiment, the preparation method of the additive is as follows:

[0099] After mixing 4-hydroxybutyl acrylate with water, forsterite powder is added, ultrasonic stirring and impregnation are performed at 40°C, and modified forsterite powder is obtained after filtering and drying. The mass ratio of 4-hydroxybutyl acrylate, forsterite powder and water addition is 0.3:1.6:8.6, and the process parameters of the ultrasonic stirring are: ultrasonic frequency is 80kHz, stirring speed is 450rpm, and the drying temperature is 110°C. The modified forsterite powder of 500-600 mesh and the graphite of 400-500 mesh are uniformly mixed in a mass ratio of 2.5:6 to obtain an additive.

[0100] The preparation method of modified phenolic resin is as follows:

[0101] Phenolic resin, 2-hydroxyethyl acrylate and initiator benzoyl peroxide were mixed in a mass ratio of 78:28:1.6, and reacted for 2 hours at a reaction temperature of 90° C. and a pH value of 8.5 in the presence of the initiator to obtain a modified phenolic resin.

[0102] Comparative Example 1:

[0103] The method of Example 2 was used to prepare the coated sand for casting, the only difference being that the modified forsterite powder in the additive in the raw material was replaced by ordinary forsterite powder in equal amounts.

[0104] Comparative Example 2:

[0105] The method of Example 2 is adopted to prepare coated sand for casting, the only difference being that the modified phenolic resin in the raw material is replaced by ordinary phenolic resin.

[0106] The coated sand prepared in Examples 1-5 and Comparative Examples 1-2 was made into sand cores for casting tests of manganese steel volutes, and the sand cores were not sprayed with any coating. The defective rate of the castings was counted, and the roughness of the castings was measured using a surface roughness profiler. For specific data, see Table 1.

[0107] Table 1 Surface roughness and defect rate of castings prepared in Examples 1-5 and Comparative Examples 1-2

[0108]

[0109] It should be noted that casting veining refers to a vein-like defect that appears on the surface or inside of a casting, which is usually caused by the obstruction of the molten metal by the sand mold or sand core during the solidification process; casting sand adhesion refers to a layer of sand particles or sand blocks that are difficult to remove adhering to the surface or part of the surface of the casting, which will affect the appearance quality and subsequent processing of the casting; casting subcutaneous pores refer to tiny pores formed under the surface of the casting, which are usually caused by the molten metal inhaling gas during the pouring process or reacting with the casting material.

[0110] It can be seen from Table 1 that the coated sand is prepared by the preparation method of the present invention, and then made into a sand core for preparing a manganese steel volute casting product. The surface roughness of the casting is significantly reduced. Due to the improvement of its surface roughness, when preparing the casting product, the generation of sand adhesion, veining, and subcutaneous pores on the surface of the casting is significantly reduced, thereby reducing the defective rate of the product.

[0111] The embodiments of the present disclosure are described above. However, these embodiments are for illustrative purposes only and are not intended to limit the scope of the present disclosure. The scope of the present disclosure is defined by the appended claims and their equivalents. Without departing from the scope of the present disclosure, a person skilled in the art may make a variety of substitutions and modifications, which should all fall within the scope of the present disclosure.

Claims

1. A coated sand for casting, characterized in that: The following raw materials are included in parts by weight: The modified phenolic resin is a modified phenolic resin obtained by reacting phenolic resin with 2-hydroxyethyl acrylate, and the mass ratio of the phenolic resin to 2-hydroxyethyl acrylate is (7-8): (2-3).

2. The coated sand for casting according to claim 1, characterized in that: The additives include modified forsterite powder and graphite, and the mass ratio of the modified forsterite powder to the graphite is (0.5-6): (4-9.5).

3. The coated sand for casting according to claim 2, characterized in that: The modified forsterite powder is a modified forsterite powder obtained by modifying forsterite powder with 4-hydroxybutyl acrylate, and the mass ratio of the added amount of the 4-hydroxybutyl acrylate to the forsterite powder is (0.1-0.5):(1-2).

4. The coated sand for casting according to any one of claims 2 to 3, characterized in that: The particle size of the modified forsterite powder is 300-600 mesh, the particle size of the graphite is 300-600 mesh, and / or, The curing agent is hexamethylenetetramine; and / or, The lubricant is calcium stearate; and / or, The silane coupling agent is any one of KH550 and KH560.

5. A method for preparing coated sand for casting, applied to the coated sand for casting as claimed in any one of claims 1 to 4, characterized in that: The steps include: S1: calcining quartz sand; S2: sieving the quartz sand calcined in step S1 and cooling it to a first temperature; S3: After the quartz sand cooled in step S2 is further cooled to a second temperature, a silane coupling agent, bisphenol A epoxy resin, modified phenolic resin, additives, a curing agent and a lubricant are added in sequence, and the mixture is stirred and mixed to obtain coated sand for casting.

6. The preparation method according to claim 5, characterized in that: In step S1, the calcination process is as follows: the calcination temperature is 700-930°C, and the calcination time is 10-30 minutes.

7. The preparation method according to claim 5, characterized in that: In step S2, the first temperature is 170-190°C.

8. The preparation method according to claim 5, characterized in that: In step S3, the second temperature is 150-160°C.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The preparation method of the modified forsterite powder comprises the following steps: mixing 4-hydroxybutyl acrylate with water, adding forsterite powder, impregnating with ultrasonic stirring at 25-80° C., filtering and drying to obtain the modified forsterite powder; The mass ratio of 4-hydroxybutyl acrylate, forsterite powder and water is (0.1-0.5): (1-2): (8-9), and the process parameters of the ultrasonic stirring impregnation are: the ultrasonic frequency is 20-80kHz, the stirring speed is 100-500rpm; the drying temperature is 80-120°C.

10. The preparation method according to any one of claims 5 to 8, characterized in that: The preparation method of the modified phenolic resin is as follows: Providing phenolic resin, 2-hydroxyethyl acrylate and an initiator, wherein the mass ratio of the phenolic resin, 2-hydroxyethyl acrylate and the initiator is (70-80): (20-30): (0.5-3); The phenolic resin and the 2-hydroxyethyl acrylate are reacted in the presence of the initiator at a reaction temperature of 60 to 100° C. and a pH value of 7 to 9 for 2 to 12 hours to obtain a modified phenolic resin; Wherein, the initiator is any one of benzoyl peroxide, dibenzoyl peroxide, and azobisisobutyronitrile.

Citation Information

Cited By

  • Precoated sand and preparation method thereof

    CN121339343A